Landing Impact Load Analysis and Validation of a Civil Aircraft Nose Landing Gear - Wenbin Liu; Youshan Wang; Yuchen Ji (Aerospace, 2023)
Landing impact load design is essential, but the process has rarely been fully described, and some designers have even neglected the differences between wheel-axle and ground-contact loads, as well as loads in the longitudinal direction, especially in experimental validations. In this paper, the entire design process of a nose landing gear is addressed, including a theoretical analysis of the unit and its experimental validation. In the theoretical analysis, a mathematical model of a two-mass system with four degrees of freedom was adopted, a computer simulation model was built accordingly, and a preliminary analysis was subsequently conducted to analyze the landing impact loads, verify the landing gear performance, and gauge the difference between the wheel-axle and ground-contact loads. For the experimental validation of the gear, a landing gear drop test was conducted in an optimized manner that emphasized pre-test preparation and during-test wheel-axle load measurement. The test results showed that both the vertical and less studied longitudinal loads, as well as the wheel-axle and ground-contact loads, had good agreement with the analysis; thus, the model, the tool, and the preliminary design were considered to be experimentally validated.